Assuming ability of youth with autism: Synthesis of methods capturing the first-person perspectives of children and youth with disabilities. (November 2019) - Tesfaye, Rackeb; Courchesne, Valerie; Yusuf, Afiqah; Savion-Lemieux, Tal; Singh, Ilina; Shikako-Thomas, Keiko; Mirenda, Pat; Waddell, Charlotte; Smith, Isabel M; Nicholas, David; Szatmari, Peter; Bennett, Terry; et al.
Most research regarding youth with autism spectrum disorder has not focused on their first-person perspectives providing limited insight into methodologies best suited to eliciting their voices. We conducted a synthesis of methods previously used to obtain the first-person perspectives of youth with various disabilities, which may be applicable to youth with autism spectrum disorder. Two-hundred and eighty-four articles met the inclusion criteria of our scoping review. We identified six distinct primary methods (questionnaires, interviews, group discussion, narratives, diaries, and art) expressed through four communication output modalities (language, sign language and gestures, writing, and images). A group of parents who have children with autism spectrum disorder were then presented with a synthesis of results. This parent consultation was used to build on approaches identified in the literature. Parents identified barriers that may be encountered during participant engagement and provided insights on how best to conduct first-person research with youth with autism spectrum disorder. Based on our findings, we present a novel methodological framework to capture the perspectives of youth with various communication and cognitive abilities, while highlighting family, youth, and expert contributions.